2022
DOI: 10.2214/ajr.21.26756
|View full text |Cite
|
Sign up to set email alerts
|

Physician Burnout in Radiology: Perspectives From the Field

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…To address burnout in the radiology department, we recommend following Chetlen et al overview on the various physician-directed and organization-directed interventions, highlighting the shared responsibility of healthcare organizations and individual physicians [27] . In addition, Canon et al provide various perspectives on the implications and strategies to mitigate physician burnout in radiology [23] . As we learned from the pandemic, teleradiology is positioned favorably among radiologists, with 64.8% reporting decreased stress levels and 64% decreased workroom interruptions [81] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address burnout in the radiology department, we recommend following Chetlen et al overview on the various physician-directed and organization-directed interventions, highlighting the shared responsibility of healthcare organizations and individual physicians [27] . In addition, Canon et al provide various perspectives on the implications and strategies to mitigate physician burnout in radiology [23] . As we learned from the pandemic, teleradiology is positioned favorably among radiologists, with 64.8% reporting decreased stress levels and 64% decreased workroom interruptions [81] .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging literature highlights burnout amongst radiologists, from trainees to department chairs [20] , [21] , [22] . It was reported that 54–72% of diagnostic and interventional radiologists exhibit burnout symptoms [23] . In the world of declining Medicare reimbursement [24] , radiologists are under more pressure to maintain a high level of accuracy while dealing with a substantially higher number of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, brain metastases are detected manually by a radiologist, and contoured by a radiation oncologist using radiation therapy planning software. 7 , 8 However, reports exist of missed small and even large brain metastases in clinical practice during the planning of Gamma Knife radiosurgery because of varied human factors. 9 , 10 Automating metastasis detection could be used as a tool to support clinicians in image evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The result is chronically de-incentivizing sick and personal days, which perpetuates a cycle of holistically overworked, burned out interventional radiology departments. 14…”
Section: Introductionmentioning
confidence: 99%